PENGELOLAAN MANAJEMEN KEUANGAN DI LEMBAGA PENDIDIKAN PADA MASA PANDEMI COVID-19 DI SDN 1 BOJONG KABUPATEN PANGANDARAN - djubardi, dodi; muhajjalina, ivy; hidayat, irpan (Journal of Management Review, 2025)
This writing was conducted to provide a descriptive analysis of the management of financial management in educational institutions during the covid-19 pandemic. Educational institutions are required to carry out the management process optimally. Schools have a duty to manage finances properly based on financial management principles so that the money that will be used can be used optimally. School financial management is based on the principles contained in the Government Regulation of the Republic of Indonesia Number 48 of 2008 concerning Education funding, namely the principles of justice, efficiency, transparency, and public accountability. The regulation also explains that these four principles are used in the process of managing school finances, starting from planning, realizing the receipt and expenditure of education funds, supervision and inspection to accountability. The results of this study indicate that SDN 1 Bojong, Langkaplancar District, Pangandaran Regency has carried out school financial management well, this can be seen from the results of interviews with the school, namely the principal and school treasurer, which shows that the financial management of SDN 1 Bojong, Langkaplancar District, Pangandaran Regency is accountable, effective. and efficient and transparent.